Genetic structure associated with habitat diversification supports the independent evolution of ecomorphs in Bradypodion pumilum. Issue 1 (9th August 2019) - Tolley, Krystal A; Hopkins, Kevin P; da Silva, Jessica M
ABSTRACT: There are notable examples of repeated evolution of ecomorphs within groups of closely related species, these are typically viewed as remarkable cases of natural selection. In most cases, directional selection for certain phenotypic traits under specific (and differing) environmental conditions is implicated. Differing ecomorphological forms for closely related species (or for populations within a species) have been documented for several lineages of South African dwarf chameleons ( Bradypodion ), although this pattern is not ubiquitous across the genus. Within one species, Bradypodion pumilum, two ecomorphs have been observed, these differ in terms of morphology, performance, ecology and habitat, yet genetic differences (mtDNA) were not apparent, with shared haplotypes across the ecomorphs. We investigated whether more sensitive genetic markers (eight microsatellite loci) would show population level structure between ecomorphs, which could indicate lack of gene flow across the ecological (habitat) boundary. Our results suggest that the two ecomorphs are distinct at a population level, implying that gene flow is absent or reduced and that the two ecomorphs are on separate evolutionary trajectories. Given that mtDNA could not detect population structure, we infer that the ecological boundary between ecomorphs is relatively recent in evolutionary history. The two ecomorphs are distinctive in terms of their morphology, ecology, habitat and functional traits, these differences are likely driven and maintained by reproductive isolation across the habitat boundary.